Choosing between city and suburb: How urbanization shapes graduates’ housing preferences - Shuxia Li; Zeqin Ye (PLoS ONE, 2025)
This study explores the housing selection mechanism of college graduates between urban and suburban areas under the background of accelerated global urbanization and regional differentiation, focusing on how they balance multiple factors such as employment opportunities, transportation convenience, living costs, career development, residential satisfaction, and family support under conditions of incomplete information and resource constraints. Research the integration of bounded rationality theory and consumer satisfaction theory to construct an analytical framework, collect data through questionnaire surveys, and use structural equation modeling for empirical testing. Research has found that external environmental factors (employment opportunities, transportation convenience, living costs, and work environment) significantly affect housing choices through direct and indirect pathways, with living costs and career planning showing a positive driving effect, while residential satisfaction plays a key mediating role. It is particularly noteworthy that family economic support not only directly affects housing decisions, but also significantly regulates the strength of the impact of living costs and employment opportunities. The research results not only expand the application of behavioral decision-making theory in the housing field but also provide important basis for government departments to optimize regional resource allocation, improve transportation networks, and formulate targeted housing policies. At the same time, it also provides practical reference for real estate developers’ market positioning and university employment guidance services. The comprehensive analysis framework established in this study also lays the methodological foundation for future largssse-scale studies that include more dynamic variables.